Eighteen-Year Effect of Androgen Therapy on Bone Mineral Density in Trans(gender) Men - Broulik, Petr Dan; Urbánek, Václav; Libanský, Petr (Hormone and Metabolic Research, 2018)
The study explores the influence of long-term androgen supplementation (18 years) on bone metabolism in trans(gender) men. Thirty five trans(gender) men aged (47±4) were treated with adequate dose of testosterone. BMD was measured by DEXA at lumbar spine and neck and T score was determined. Biochemical parameters of bone turnover were measured in all patients. As compared with female and male age matched controls they showed a not significantly different T-score at spine [1.213±0.15 in trans(gender) men vs. 1.192±0.19 in females and 1.203±0.06 g/cm2 in males (p<0.01)]. BMD in the hip skeleton in trans(gender) men (0.950±g/cm2) was statistically higher than females (0.822±0.09) but not statistically different from normal males 0.988±0.06). Circulating biochemical markers of bone formation, and resorption were not different between the trans(gender) men, and matched controls. We conclude that BMD at the hip (site rich in cortical bone) after adequate dose of testosterone therapy is higher while it is not different at the spine (trabecular bone) in trans(gender) men even after 18 years of testosterone administration.
Keywords: trans(gender) men; bone mineral density; testosterone